2017
DOI: 10.1155/2017/7085392
|View full text |Cite
|
Sign up to set email alerts
|

Study on Impact Behavior and Impact Force of Bridge Pier Subjected to Vehicle Collision

Abstract: The increasing occurrence of vehicle-pier collision accidents has significant influences on the safety of bridge structures. In order to study the impact behavior of bridge piers, a vehicle-double-pier collision numerical model was developed by LS-DYNA. Nonlinear material constitutive laws considering the strain-rate effect were used. The reliability of numerical analyses was validated. Parametric studies were carried out to investigate the effects of impact velocity, impact mass, and concrete and steel streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Studies (Aflatooni et al, 2012; Zhou et al, 2017) have shown that RC piers could sustain different damage levels due to various vehicle impact forces, which affected subsequent service life of the impacted piers. Moreover, studies (Sharma et al, 2012; Zhou et al, 2017) have shown that the vehicle impact force was greatly affected by impact velocity and impact mass. A qualitative damage classification of the impacted pier was defined in this section.…”
Section: Damage Assessment Of Impacted Piersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (Aflatooni et al, 2012; Zhou et al, 2017) have shown that RC piers could sustain different damage levels due to various vehicle impact forces, which affected subsequent service life of the impacted piers. Moreover, studies (Sharma et al, 2012; Zhou et al, 2017) have shown that the vehicle impact force was greatly affected by impact velocity and impact mass. A qualitative damage classification of the impacted pier was defined in this section.…”
Section: Damage Assessment Of Impacted Piersmentioning
confidence: 99%
“…Pham and Hao (2017) performed numerical analyses on the plastic hinges and inertia forces in RC beams under impact loads. In addition, there are also many other publications that reported numerical studies on impact behaviors of RC piers (Chen et al, 2016; Chung et al, 2014; Zhou et al, 2017). However, few numerical studies describe well the failure process and damage assessment of the impacted piers.…”
Section: Introductionmentioning
confidence: 99%
“…Do et al [17] studied the failure model and dynamic response of a bridge pier through numerical simulation and experiment. Zhou et al [18] used the parameterization method to study the collision response behavior of a vehicle hitting a bridge pier and its structural damage mechanism. Studies have shown that, after a ship hits a bridge pier, the impact resistance of the bridge structure can be improved in two ways: one is to improve the anticollision performance of the bridge, and the other is to set up an anticollision facility.…”
Section: Introductionmentioning
confidence: 99%
“…2. Zhou et al (2017) analyzed the impact behavior of bridge piers for the vehicle-pier collision accidents, and developed a vehicle-double-pier collision numerical model. Zhou et al (2019) studied the collision force of reinforced concrete piers under cumulative ship collision by using the combining theoretical deduction with numerical analysis.…”
Section: Introductionmentioning
confidence: 99%